Monitoring and Evaluation Following Health Protocol - Mayang Pranita; Suci Yustrianti Marpaung; Rini Deby Astria Lubis; Nisa Ardana (Pena Cendekia Insani, 2021)
The problem of the prevalence of Covid-19 in the world and in Indonesia is increasing, the health protocol is to prevent the spread of Corona virus infection to the wider community. The purpose of this study is to monitor and evaluate the Covid-19 health protocol in the city of Medan. This study is a quantitative study with a cross-sectional design. This research was conducted in the city of Medan, the time of this research in June 2021-July 2021. The population in this study were all facilities in the city of Medan. The sample in this study were 59 locations in the city of Medan. The sampling technique in this study is by using direct observation techniques. The data analysis in this research is univariate analysis using descriptive analysis. The results of this study are that there are 45 COVID-19 prevention posters, 46 facilities temperature checks, 49 facilities keeping a 1 meter distance, 48 facilities wearing masks, 38 hand washing facilities, and 49 no disinfectants. facility. Visitors do not want to check temperatures as many as 30 people, some respondents who use masks in public facilities as many as 29 people, visitors do not want to wash their hands when entering public facilities as many as 26 people, all respondents want to use hand sanitizer in public facilities as many as 29 people, respondents only some of them want to do social distancing as many as 32 people, all respondents avoid shaking hands as many as 33 people, and none of the respondents want to bring their own equipment (worship equipment) as many as 28 people. It is hoped that health cadres will provide counseling about good and correct 3M protocols so that they are expected to be able to prevent the transmission of Covid-19.